"It's not as easy as saying, 'just get them to eat more veggies'": Exploring healthy eating in residential care in Australia. (1st October 2017) - Cox, Rachael; Emond, Ruth; Punch, Samantha; McIntosh, Ian; Hall, Kate; Simpson, Angela; Skouteris, Helen
Abstract: Young people living in residential out-of-home care (henceforth OoHC) are at increased risk of becoming overweight or obese. Currently, recognition of the everyday mechanisms that might be contributing to excess weight for children and young people in this setting is limited. The aim of this study was to better understand the barriers and complexities involved in the provision of a 'healthy' food environment in residential OoHC. Heightening awareness of these factors and how they might compromise a young person's physical health, will inform the development, refinement and evaluation of more sensitive and tailored weight-related interventions for this population. The paper presents a nuanced picture of the complexity of everyday food routines in residential care, and illustrates the ways in which food is 'done' in care; how food can be both symbolic of care but also used to exercise control; the way in which food can be used to create a 'family-like' environment; and the impact of traumatic experiences in childhood on subsequent behaviours and overall functioning in relation to food. It is argued that a health agenda designed for a mainstream population ignores the very complex relationship that children in residential OoHC may have with food. It is recommended that future intervention approaches account for personal food biographies, trauma and children's social backgrounds and how these are implicated in everyday practices and interactions around food.